SCIENTIFIC JUSTIFICATION OF A COMPREHENSIVE PREVENTIVE STRATEGY TO REDUCE THE RISKS OF PREMATURE AGING IN THE ARCTIC ZONE - Savchenko, Oleg Andreevich; Novikova, Irina Igorevna; Chuenko, Natalia Fedorovna (Medicine in Kuzbass, 2026)
The development of the Arctic zone is associated with the complex impact of extreme natural and climatic and production factors, which have a synergistic effect, leading to the development of the phenomenon of accelerated «Arctic» aging. The hygienic regulation, which is carried out on a factor-by-factor basis, does not fully take into account the synergistic nature of the expected potential effects specific to the Arctic zone, which undoubtedly makes this research area relevant.The purpose of the study is to provide a scientific basis for a set of preventive measures for nutritional correction in the Arctic zone, taking into account the specific features of nutrition and the molecular mechanisms of «Arctic» aging.Materials and methods. A systematic literature review (30 sources, 2015-2025) and a 28-day experiment on 48 male Wistar rats were conducted. The animals were divided into 4 groups: intact control in comfortable conditions (K2), control in Arctic conditions (K1, temperature +4-6°C, «polar night» and «day» regimes), and two experimental groups in Arctic conditions, which received a specially developed vitamin and mineral complex «Arctic TROFI» in the doses recommended by the developers (E1) and 10-fold (E2). Physiological, biochemical, hormonal, hematological indicators and organ morphology were evaluated. The experiment was conducted in accordance with the principles of the European Convention for the Protection of Vertebrate Animals Used for Experimental Purposes (Strasbourg, 1986), and after approval by the institute's ethics committee.Results and their discussion. Modeling of arctic conditions caused a stress reaction and signs of accelerated aging: hypothermia, hyperglycemia (an increase of 118%, p < 0.05), an increase in ALT/AST activity by 1.8-2.2 times, leukopenia, and structural damage to organs. An imbalance in the cortisol-testosterone system was detected (an increase in cortisol by 24%, and a decrease in testosterone by 31% in K1 compared to K2, p < 0.05). Nutritional correction had a dose-dependent protective effect: it normalized thermoregulation, reduced glucose and cytolysis levels, modulated hormonal status (decreased cortisol, increased testosterone), and reduced morphological damage.Conclusion. It has been established that premature aging in the Arctic zone is caused by the synergism of extreme factors and micronutrient deficiencies. The experiment has confirmed the effectiveness of nutritional correction. The features of prevention based on the assessment of combined risks, mandatory micronutrient support, predictive monitoring, and personalization of measures have been scientifically substantiated. The implementation of this approach will ensure a transition to health management and the preservation of professional longevity in the Arctic.
Keywords: model conditions of the Arctic zone; rats; subchronic experiment; stress; nutritional correction; prenosological monitoring; risks of premature aging; preventive medicine